Fibrin Derivatives, Plasma Hemoglobin and Glomerular Fibrin Deposition in Experimental Intravascular Coagulation - Beller, F. K; Theiss, W (Thrombosis and Haemostasis, 1973)
Plasma fibrinogen, circulating fibrinmonomers (as indicated by a positive ethanol gelation test), fibrinolysis breakdown products and plasma hemoglobin were assayed in 122 rats subjected to endotoxin injection or infusion. The results were correlated with the quantitative measurement of glomerular fibrin deposition. Based on these data four groups were determined : consumption coagulopathy and three stages of increasing severity of disseminated intravascular coagulation (DIG).Consumption coagulopathy was defined by a decrease in plasma fibrinogen and a positive ethanol gelation test in the absence of glomerular fibrin deposition. Plasma hemoglobin and fibrinolysis breakdown products were normal or only slightly increased.DIG as characterized by glomerular fibrin deposition was defined as moderate (1 to 20% glomeruli showing fibrin strands), intermediate (21 to 80%), and severe (81 to 100%). Decrease in plasma fibrinogen and frequence of a positive ethanol gelation test in all stages of DIG were only slightly different from the findings in consumption coagulopathy. However, a sharp increase in plasma hemoglobin levels was noted when glomerular fibrin deposition did occur even in small amounts. At this time only a moderate increase was noted in fibrin(ogen) breakdown products. These two parameters increased only slightly in the group of intermediate DIG. Severe DIG was characterized by a massive increase in fibrin (ogen) breakdown products and high levels of plasma hemoglobin.